1987
DOI: 10.3354/meps039153
|View full text |Cite
|
Sign up to set email alerts
|

Cyclonic cold-core eddy in the eastern North Atlantic. II. Nutrients, phytoplankton and bacterioplankton

Abstract: A cyclonic cold-core eddy in the Northeast Atlantic of about 100 km in diameter at the sea surface was investigated in May 1985, approximately 3 wk after it had separated from the Polar Front. A strong thermocline, which was shallower but more pronounced than in the ambient water, separated a warm surface layer within the eddy from deeper cold water, while horizontal salinity gradients marked the boundary to the ambient water. The cold-core eddy could be distinguished from amblent Northeast Atlantic water in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 19 publications
5
42
0
Order By: Relevance
“…‡ Minimum front length of 1,800 km, if a simple linear shape between 20ЊW and 40ЊW and minimum front width of 55 km, calculated by a marked depression of isotherms ( centration, and picoplankton biomass could be due to surface heating and mixing processes (Harris et al 1997) or the dynamic equilibrium with the surrounding waters (Ring Group 1981) when the eddy depicts a low-energy stage. High heterotrophic bacterial abundance has been observed both in mature (Harris et al 1997) and in young eddies (Lochte and Pfannkuche 1987). The mean bacterial abundance within the photic layer observed by Campbell et al (1997) in the oligotrophic subtropical central Pacific was 4.2 ϫ 10 5 cell ml Ϫ1 , similar to the values measured in this study in the oligotrophic waters outside the mesoscale features (4.4 ϫ 10 5 cell ml…”
supporting
confidence: 78%
See 1 more Smart Citation
“…‡ Minimum front length of 1,800 km, if a simple linear shape between 20ЊW and 40ЊW and minimum front width of 55 km, calculated by a marked depression of isotherms ( centration, and picoplankton biomass could be due to surface heating and mixing processes (Harris et al 1997) or the dynamic equilibrium with the surrounding waters (Ring Group 1981) when the eddy depicts a low-energy stage. High heterotrophic bacterial abundance has been observed both in mature (Harris et al 1997) and in young eddies (Lochte and Pfannkuche 1987). The mean bacterial abundance within the photic layer observed by Campbell et al (1997) in the oligotrophic subtropical central Pacific was 4.2 ϫ 10 5 cell ml Ϫ1 , similar to the values measured in this study in the oligotrophic waters outside the mesoscale features (4.4 ϫ 10 5 cell ml…”
supporting
confidence: 78%
“…Boyd et al (1997) observed little variation between rates of new production inside and outside of this eddy. By contrast, high differences between cyclonic eddies and surrounding waters have been observed in primary production rates and Chl a concentration (e.g., Falkowski et al 1991;McNeil et al 1999) and bacterial abundance (Lochte and Pfannkuche 1987). The TOPEX-POSEIDON altimetry data received indicated that Leticia was detected for ϳ400 d (24 May 1998-28 June 1999) but with a disminishing signal for ϳ3 months after the cruise (Mouriño et al pers.…”
mentioning
confidence: 99%
“…Lochte and Pfannkuche (1987) observed nutrient depletion in the upper 50 m within the center of a cyclonic eddy. They proposed that the physical isolation of eddy surface waters due to the formation of a shallow thermocline lead to rapid utilization of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Within the eddy centre, we noticed the characteristic odour of plankton. Using the CTD profiles to obtain a rough idea about the extension of the eddy, stations were selected for biological sampling along the SW-NE section (Stn 159 to 164) to study the eddy's ecosystem (Beckmann et al 1987, Lochte & Pfannkuche 1987.…”
Section: Methods and Observationsmentioning
confidence: 99%
“…Some of them, for instance Gulf Stream rings, have a lifetime from a month to more than a year (see reviews in Robinson 1983). An example of such an oceanic ring is described in this and the following 2 articles (Beckmann et al 1987, Lochte & Pfannkuche 1987. Although a turbulent element, the geostrophy and the long Lifetime allow such an eddy to be considered as a systematic and orderly phenomenon.…”
Section: Introductionmentioning
confidence: 99%